Бенчмаркінг якості фізико-математичної освіти в сучасній вищій школі - Кюрчев, Володимир Миколайович; Кюрчев, Владимир Николаевич; Kiurchev, Volodymyr; Kiurchev, Volodymyr; Ломейко, Александр Петрович; Lomeiko, Oleksandr; Сосницька, Наталя Леонідівна; Сосницкая, Наталья Леонидовна; Sosnytska, Natalia; Данченко, Микола Миколайович; Данченко, Николай Николаевич; Danchenko, Mykola; et al. (My University, 2021)
UK: Проаналізовані сучасні проблеми з фізико-математичної освіти в світі і Україні, вивчені основні причини загострення конкуренції на ринку освітніх послуг та знайдені ефективні методи подолання кризисних станів та перспективні напрями вдосконалення навчального процесу в ВНЗ. Досліджений рівень підготовки з математики і фізики у випускників середніх шкіл в Україні та у студентів-першокурсників ТДАТУ. Дана оцінка першим результатам впровадження бенчмаркінгу фізико-математичної освіти в ТДАТУ та визначені стратегічні напрями подальших бенчмаркінгових досліджень. EN: The modern problems of physical and mathematical education in the world and Ukraine are analyzed, the main reasons for the intensification of competition in the market of educational services are studied and effective methods of overcoming crisis situations and perspective directions of improving the educational process in universities are found. The level of training in mathematics and physics among high school graduates in Ukraine and first-year students of TSATU has been studied. The evaluation of the first results of the introduction of benchmarking of physical and mathematical education in TSATU is given and the strategic directions of further benchmarking researches are determined.
Keywords: математична і фізична освіта; вища освіта; бенчмаркінг; вхідний контроль; адаптаційні курси; mathematical and physical education; higher education; benchmarking; entrance control; adaptation courses